2018
DOI: 10.1130/b31818.1
|View full text |Cite
|
Sign up to set email alerts
|

Global perturbation of the marine calcium cycle during the Permian-Triassic transition

Abstract: A negative shift in the calcium isotopic composition of marine carbonate rocks spanning the end-Permian extinction horizon in South China has been used to argue for an ocean acidification event coincident with mass extinction. This interpretation has proven controversial, both because the excursion has not been demonstrated across multiple, widely separated localities, and because modeling results of coupled carbon and calcium isotope records illustrate that calcium cycle imbalances alone cannot account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 74 publications
(124 reference statements)
3
44
0
Order By: Relevance
“…A similar trend is observed in the calcium isotopic compositions of conodont apatite from the Meishan GSSP (Hinojosa et al, 2012). This pattern was also found in Turkey, Italy, and Oman in terms of the direction, magnitude, and timing of the calcium isotope excursion (Lau et al, 2017;Silva-Tamayo et al, 2018). Based on updated modeling experiments, Silva-Tamayo et al (2018) concluded that the observed parallel negative excursions in carbonate δ 44/40 Ca and δ 13 C are best explained by a series of consequences arising from Siberian Traps volcanic CO 2 release.…”
Section: Ocean Acidificationsupporting
confidence: 77%
See 2 more Smart Citations
“…A similar trend is observed in the calcium isotopic compositions of conodont apatite from the Meishan GSSP (Hinojosa et al, 2012). This pattern was also found in Turkey, Italy, and Oman in terms of the direction, magnitude, and timing of the calcium isotope excursion (Lau et al, 2017;Silva-Tamayo et al, 2018). Based on updated modeling experiments, Silva-Tamayo et al (2018) concluded that the observed parallel negative excursions in carbonate δ 44/40 Ca and δ 13 C are best explained by a series of consequences arising from Siberian Traps volcanic CO 2 release.…”
Section: Ocean Acidificationsupporting
confidence: 77%
“…This pattern was also found in Turkey, Italy, and Oman in terms of the direction, magnitude, and timing of the calcium isotope excursion (Lau et al, 2017;Silva-Tamayo et al, 2018). Based on updated modeling experiments, Silva-Tamayo et al (2018) concluded that the observed parallel negative excursions in carbonate δ 44/40 Ca and δ 13 C are best explained by a series of consequences arising from Siberian Traps volcanic CO 2 release. These included a temporary decrease in seawater δ 44/40 Ca due to short-lived ocean acidification and a more protracted increase in calcium isotope fractionation associated with a shift toward more primary aragonite in the sediment and, potentially, subsequently elevated carbon saturation states caused by the persistence of elevated CO 2 delivery from volcanism.…”
Section: Ocean Acidificationmentioning
confidence: 73%
See 1 more Smart Citation
“…; Silva‐Tamayo et al . ). Another notable feature is the dominance of aragonite taxa in the benthic communities, with the exception of the Huangzhishan Formation fauna, suggesting a high pH of benthic ecosystems in the extinction aftermath globally.…”
Section: Resultsmentioning
confidence: 97%
“…The end‐Permian mass extinction (EPME), one of the most remarkable biological events in the Phanerozoic Eon, considerably altered evolutionary processes in marine ecosystems and marked the transition from Palaeozoic‐type marine ecosystems to the ‘modern’ Mesozoic and Cenozoic‐type marine ecosystems (Sepkoski 1981; Chen & Benton 2012; Payne et al 2014; Stanley 2016; Brayard et al 2017). It is argued that ecosystem collapse (or extinction) was triggered by synergistic stresses, such as anoxia (Wignall & Twitchett 1996; Isozaki 1997; Winguth & Winguth 2012; Huang et al 2017b), global warming (Joachimski et al 2012; Sun et al 2012; Garbelli et al 2016; Brand et al 2016) and possible ocean acidification (Payne et al 2007, 2010; Hinojosa et al 2012; Kershaw et al 2012; Clarkson et al 2015; Silva‐Tamayo et al 2018). Marine ecosystems involve biotic and abiotic components, which need to be considered together when discussing extinction patterns and processes.…”
mentioning
confidence: 99%